Selection of purification and formation of double haploid Toraja endemic black rice through anther culture. Issue 1 (April 2020) - Haring, F; Rantetandung, S; Riadi, M; Rafiuddin,; Sjahril, R
Abstract: To maximize the potential of Ko'bo, plant breeding was involved to produce the identic color of rice grains, which is full black. Anther culture is a method that is considered effective in plant breeding. This study aimed to find the most suitable combination of growth regulators in the calli induction of Ko'bo rice anther and observe the calli growth response in a regeneration medium. Calli induction experiment used N6 medium with a combination of auxin (2, 4-D 1-3 mg L −1 ) and cytokinin (kinetin 0.5-1 mg L −1 and BAP 0.5-1 mg L −1 ). Calli regenerated in MS medium, added with 0.5 mg NAA L −1 + kinetin 0.5 mg L −1 + BAP 1.5 mg L −1 . The experiment was arranged in a Completely Randomized Design. The experimental unit was a petri dish, containing ± 250 anthers. The highest calli induction was 13.33%, obtained from a combination of 2, 4-D 3.0 mg L −1 + kinetin 1.0 mg L −1 . All regenerated plantlets were albino.